Performance of a Rapid Self-Test for Detection of Trichomonas vaginalis in South Africa and Brazil - Jones, Heidi E. (American Society for Microbiology, 2013)
Women participating in studies in Brazil (n = 695) and South Africa (n = 230) performed rapid point-of-care tests for Trichomonas vaginalis on self-collected vaginal swabs. Using PCR as the gold standard, rapid self-testing achieved high specificity (99.1%; 95% confidence interval [CI], 98.2 to 99.6%) and moderate sensitivity (76.7%; 95% CI, 61.4 to 88.2%). These tests may be considered an alternative to syndromic management in resource-poor settings.